$R-D$-Systems and Irzhina’s branching processes - Safaryan, R. G. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
For parabolic equations, containing a nonlinear part of a special form, one constructs a probabilistic representation of the solution in the form of the mathematical expectation of some functional of the trajectories of a branching process with a continuous set of particle types.